Efficient synthesis of 4-substituted-ortho-phthalaldehyde analogues: toward the emergence of new building blocks - Moitessier, Clémence; Rifai, Ahmad; Danjou, Pierre-Edouard; Mallard, Isabelle; Cazier-Dennin, Francine (Beilstein Journal of Organic Chemistry, 2019)
4-Methoxy-ortho-phthalaldehyde and 4-hydroxy-ortho-phthalaldehyde are potentially useful molecules for fluorimetric analysis of a variety of amines and for the elaboration of complex molecular architectures. Nevertheless, literature generally describes their synthesis in very low yield (below 5%), mainly due to the inefficiency of the last oxidation step. In this paper, we report a reliable synthesis of 4-substituted-ortho-phthalaldehyde analogues in 51% overall yield owing to the addition of a protecting step of the unstable key intermediate 4,5-dihydroisobenzofuran-5-ol. Oxidation and deprotection steps were also studied in order to provide an effective availability of these two dialdehyde compounds that may increase their future applications.
Keywords: demethylation; hydroxy group protection; 4-hydroxy-ortho-phthalaldehyde; ortho-phthalaldehyde; oxidation

(untitled) - Zuman, P.; Salem, N.; Kulla, E. (Electroanalysis, 2009)

(untitled) - Rönnberg, A. L.; Hansson, C.; Drakenberg, T.; Håkanson, R. (Anal. Biochem., 1984)

(untitled) - Yoshimura, T.; Kaneuchi, T.; Miura, T.; Kimura, M. (Anal. Biochem., 1987)

(untitled) - Oh, J.-A.; Shin, H.-S. (J. Chromatogr. A, 2012)

(untitled) - Zandy, S. L.; Doherty, J. M.; Wibisono, N. D.; Gonzales, R. A. (J. Chromatogr., B, 2017)

(untitled) - Zuman, P. (Chem. Rev., 2004)

(untitled) - Allin, S. M.; Hodkinson, C. C.; Taj, N. (Synlett, 1996)

(untitled) - Kulla, E.; Zuman, P. (Org. Biomol. Chem., 2008)

(untitled) - Nakao, M.; Nishikiori, N.; Nakamura, A.; Miyagi, M.; Shibata, N.; Kitaike, S.; Fukui, M.; Ito, H.-O.; Sano, S. (SynOpen, 2018)

(untitled) - Sun, F.-G.; Ye, S. (Synlett, 2011)

(untitled) - Aitken, R. A.; Hauduc, C.; McLennan, R. S.; Slawin, A. M. Z.; Wilson, H. S. (Tetrahedron Lett., 2015)

(untitled) - Reddy, P. M.; Ho, Y.-P.; Shanker, K.; Rohini, R.; Ravinder, V. (Eur. J. Med. Chem., 2009)

(untitled) - Kaitz, J. A.; Diesendruck, C. E.; Moore, J. S. (Macromolecules, 2013)

(untitled) - Khan, A. M.; Proctor, G. R.; Rees, L. (J. Chem. Soc. C, 1966)

(untitled) - Taylor, E. C.; Jennings, L. D.; Mao, Z.; Hu, B.; Jun, J.-G.; Zhou, P. (J. Org. Chem., 1997)

WO Patent - Yu, W.; Tong, L.; Chen, L.; Kozlowski, J. A.; Lavey, B. J.; Shih, N. Y.; Madison, V. S.; Zhou, G.; Orth, P.; Guo, Z.; Wong, M. K. C.; Yang, D. Y.; et al. (Hydantoin Derivatives for the Treatment of Inflammatory Disorders, 2006)

(untitled) - Cao, L.; Isaacs, L. (Org. Lett., 2012)

(untitled) - Majdoub, M.; Loupy, A.; Petit, A.; Roudesli, S. (Tetrahedron, 1996)

(untitled) - Hayakawa, K.; Yamaguchi, Y.; Kanematsu, K. (Tetrahedron Lett., 1985)

(untitled) - Wenkert, E.; Khatuya, H. (Synth. Commun., 1999)

(untitled) - Zhu, P.; Lu, K.; Wang, D.-H. (ACS Symp. Ser., 2007)

WO Patent - Isogai, K.; Tsumaki, H.; Eguchi, D.; Fukuyama, S. (Crystalline Hydrate of Ortho-Phthalaldehyde, Disinfecting Agent and Biocide Containing Same, and Method for Manufacturing Ortho-Phthalaldehyde, 2012)

(untitled) - Borisenko, K. B.; Zauer, K.; Hargittai, I. (J. Phys. Chem., 1996)

(untitled) - Danjou, P.-E.; De Leener, G.; Cornut, D.; Moerkerke, S.; Mameri, S.; Lascaux, A.; Wouters, J.; Brugnara, A.; Colasson, B.; Reinaud, O.; Jabin, I. (J. Org. Chem., 2015)

(untitled) - Fang, Z.; Zhou, G.-C.; Zheng, S.-L.; He, G.-L.; Li, J.-L.; He, L.; Bei, D. (J. Mol. Catal. A: Chem., 2007)

(untitled) - Boovanahalli, S. K.; Kim, D. W.; Chi, D. Y. (J. Org. Chem., 2004)

(untitled) - Martín-Matute, B.; Nevado, C.; Cárdenas, D. J.; Echavarren, A. M. (J. Am. Chem. Soc., 2003)

(untitled) - Wu, H.-J.; Yen, C.-H.; Chuang, C.-T. (J. Org. Chem., 1998)

(untitled) - Bhattacharjee, D.; Popp, F. D. (J. Heterocycl. Chem., 1980)

(untitled) - Sánchez-Larios, E.; Holmes, J. M.; Daschner, C. L.; Gravel, M. (Org. Lett., 2010)